PFAS exposure during pregnancy: Implications for placental health and functioning - Khan, Sadia; Ouidir, Marion; Lemaitre, Nicolas; Jovanovic, Nicolas; Bayat, Sam; Lyon-Caen, Sarah; Hoffmann, Pascale; Desseux, Morgane; Thomsen, Cathrine; Couturier-Tarrade, A.; Småstuen Haug, Line; Valmary-Degano, Séverine; et al. (Environment international, 2025)
[Display omitted] •First study about the effects of PFAS on human placental histological parameters.•PFTrDA, PFHxPA, PFHpA, and 6:2 diPAP associated with fetal − maternal exchanges.•Women in the moderate/high exposure cluster had reduced placental weight. Animal studies have linked prenatal poly- and perfluoroalkyl substances (PFAS) exposures with impaired placental structure and function. In humans, only few studies have investigated such associations. We studied whether PFAS, individually and as a mixture, affected placental function. In 367 pregnant women, we quantified 13 PFAS in serum collected at 19.3 gestational weeks (median). Placental weight was recorded at delivery. Histological examination of placental tissues allowed estimation of vascular perfusion (percentage of villi with syncytial knots, capillary density, intervillous space) and placental aging (fibrin deposition, calcification). Associations between PFAS and each of these parameters were assessed using adjusted linear, logistic regressions and mixture modeling through cluster analysis and Bayesian kernel machine regression (BKMR). PFHxPA quantification (yes versus no) was associated with an increase in the percentages of villi with syncytial knots (β = 6.0% [95% CI: 1.1; 11]) and reduced intervillous spaces (β = 4.7% [95% CI: 0.1; 9.3]). A similar pattern was observed with PFHpA. Isolated associations were observed between PFTrDA and percentages of villi with syncytial knots (β = 8.6% [95% CI: 2.2; 15]) and 6:2diPAP and capillary density (β = −17% [95% CI: −30; −4.6]). Cluster analysis suggested that women in the moderate-to-higher PFAS exposure group had on average lower placental weight (β= −30 g [95% CI: −56; −4.3]), compared to those in the lower exposure group. Pregnancy PFAS levels were associated with placental parameters of fetal-maternal exchange, highlighting their broad physiological impacts.